The nature of causality and effectuation in the context of service innovation in small independent firms - Shishan, Farah (2019)
This thesis examines the nature of causality and effectuation in the context of service innovation in small independent firms. The purpose of the study is to uncover whether and, if so, how causal and effectual logics co-exist, based on an analysis of strategy and decision-making behaviours associated with resource utilisation. This is examined by adopting the lens of effectuation theory (Sarasvathy, 2001). The research has three main objectives: (i) To understand firms’ behaviours in relation to resource utilisation for service innovation, focusing on the underpinning logics; (ii) To analyse interrelations in the use of causal and effectual logics; and (iii) To evaluate the conditions underlying such interrelations and assess their effects on resource utilisation and service innovation. Taking the view that reality is socially constructed and subjective, a multiple case study methodology is employed. The sample consists of nine small independent hotels, all located in the United Kingdom (UK). Data is collected through in-depth semi-structured interviews and observations. Afterwards, common themes are identified through systematic stages and an iterative process of analysis. The findings of this thesis suggest four types of causal–effectual logic interrelations. These are denoted as follows: (1) dominated by causal logic, (2) dominated by effectual logic, (3) hybrid logic – dominated by effectual logic, and (4) hybrid logic – dominated by causal logic. Deeper analysis of the interrelations confirms that a hybrid logic exists between causal and effectual systems. Moreover, this study suggests that hybridity can be found in two distinctive types, determined by their different characteristics and behaviours. One type shows hybridity through a path moving from effectual logic to causal logic. Another type shows hybridity through the dominance of causal logic. However, this type borrows some effectual-logic-related activities on different occasions. Therefore, the findings show two different routes in regard to the utilisation of resources for service innovation by small independent firms in the hospitality industry. Furthermore, based on the study’s findings, the thesis suggests that organisations that are underpinned by different logics have fundamentally different approaches to service innovation. The adopted logic acts as a mirror to the service innovation approach. Based on the four interrelation types, those dominated by causal logic demonstrate an exploitative proactive service innovation approach, while those dominated by effectual logic show an exploitative reactive service innovation approach. Further, although both hybrid logic interrelation types demonstrate a combined exploitative proactive and reactive approach, the dominant logic in each type will dictate which of the approaches outweighs the other. In this sense, we find that hybridity reflects a greater degree of innovation due to its combined proactive and reactive service innovation approach. Finally, the study found that the different interrelations between both logics emerge due to three conditions: (i) behaviours and practices, (ii) nature of resources, and (iii) management attitude. The study aims to contribute to the existing literature by filling three gaps. Firstly, it focuses on the interrelations between effectual and causal logics. In addition, it develops and proposes a more nuanced understanding of hybridity (Reymen et al., 2015; Read et al., 2009b; Perry et al., 2012). Secondly, it attends to the current lack of effectuation theory literature in relation to service innovation in small firms (Ortega et al., 2017; Berends et al., 2014; Alonso et al., 2017), specifically in small independent firms in the hospitality industry (Grissemann and Stokburger-Sauer, 2012; López-Fernández et al., 2011; Orfila-Sintes and Mattsson, 2009). It addresses this gap by looking at diverse service innovation approaches based on the unravelled four types of causal–effectual logic interrelations. Thirdly, it proceeds from studying the interrelations between both logics to focus on the examination of the different conditions underpinning such interrelations (Stroe et al., 2018; Ortega et al., 2017; Laine and Galkina, 2017). Identifying such conditions is essential to building our understanding of firms’ behaviours in terms of how resources are used to innovate. This thesis also has important practical implications. The study provides recommendations targeted at small independent firm owners in regard to resource utilisation and service innovation. It proposes various strategies for the four types of causal–effectual logic interrelations in order to increase the scope of service innovation. For example, it recommends utilising the owners’ social and professional networks for different types of collaborations. It also recommends continuously evaluating the external environment for free or exchangeable resources to add new services or reach new customers. Additionally, some of these practical implications for small independent firm owners are aimed to encourage owners to develop their ability to combine both logics by training themselves to plan and adapt, to work towards their visions and to embrace unplanned opportunities and available resources. Further, the detailed understanding of intangible resource utilisation and the role played by management attitude in relation to hybridity also leads to vital practical implications. For example, small business owners should consider the role of their intangible resources, particularly the owners’ or managers’ personalities, dedication, persistence and networking abilities in the use of both logics. Being aware of this enables the owners and managers to stop fixating on their lack of tangible resources and broaden their perspectives and appreciation of intangible resources and management attitude due to their critical role in interrelating both logics. Consequently, this broadens their scope of innovation by pushing them to be proactive and reactive in finding opportunities and utilising the available resources to innovate.